Homiletics and hermeneutics : four views on preaching today - Gibson, Scott M., 1957-; Kim, Matthew D., 1977- (Secunderabad : Good shepherd nooks, 2022)
"Four preaching experts present and defend their approach to homiletics, introducing pastors and ministry students to the hermeneutics of preaching"--
Redemptive-historic view / by Bryan Chapell -- Christiconic view / by Abraham Kuruvilla -- Theocentric view / by Kenneth Langley -- Law-Gospel view / by Paul Scott Wilson.
Includes bibliographical references and indexes.
Keywords: Bible -- Homiletical use; Bible -- Hermeneutics; Preaching; Doctrinal preaching; Hermeneutics -- Religious aspects -- Christianity